The role of thermal insulation layers and the integration of solar energy in temporary heating systems - Selimaj, Rexhep; Osmanaj, Sabrije (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper examines thermal insulation strategies for building walls and the integration of solar heating systems to improve the performance of temporary heating systems in residential buildings in Kosovo. A two-story house was used as the case study, simulating four different scenarios of thermal insulation layer placement in the walls with different capacities of the heating system. The proposed thermal balance method of the building takes into account the arrangement of thermal insulation layers and their impact on the building’s energy savings. The results indicate that external insulation offers the best balance between heat retention and energy efficiency, while internal insulation enables faster heating and a shorter time to reach the desired temperature. Under low-temperature conditions, solar energy was analyzed and integrated as an additional source to enhance the heating system capacity and reduce electricity consumption. Simulation results demonstrate further improvement in system performance, enabling optimized operating schedules and a significant reduction in energy consumption.